Encyclopedia of Education and Information Technologies - Tatnall, Arthur (Springer International Publishing AG, 2020)
This encyclopedia aims to offer researchers an indication of the breadth and importance of information systems in education, including the way IT is being used, and could be used to enable learning and teaching.  The encyclopedia covers all aspects of the interaction between education and information technologies, including IT in kindergartens, primary and secondary schools, universities, training colleges, industry training, distance education and further education.  It also covers teaching and computing, the use of IT in many different subject areas, the use of IT in educational administration, and national policies of IT and education.